Energy saving model of the heating cylindrical warmly exchange module tom – 1 - Korabeinikova, V.K.; Voronov, E.N. (Publishing House of the KarSU named after E.A.Buketov, 2012)
For effective burning of low-grade Kuznetsk coal, according to Voronov E.N. proposal the heating cylindrical heat exchange module TOM-1 is developed and approved. Which distinctive feature is the cone-shaped fire chamber with a grid-iron motionless not failure lattice and a loading ring for burning in a layer of polyfractional coal in the dense clamped bed. And also a design of heat exchange sections of heating trumpet elements with modular distributive water collectors in a look of «a water shirt», carrying out as well a role of a brickwork envelope of a copper. As thermal isolation the thin layer of corundum is used. This design is the representative of energy saving technology
Keywords: energy saving; cylindrical heat exchange module; polyfractional coal; cone-shaped fire chamber; heating trumpet element; a water shirt